Deoxyribonucleic Acid of Anaplasma marginale - Senitzer, D. (1972)
Deoxyribonucleic acid from isolated marginal bodies and calf erythrocytes infected with Anaplasma marginale is found to be double stranded and to contain 51 moles per cent guanine plus cytosine.